Intrinsic valley Hall transport in atomically thin MoS2 - Zefei Wu (Nature Portfolio, 2019)
Electrons hopping in two-dimensional honeycomb lattices possess a valley degree of freedom. Here, the authors observe room-temperature valley Hall transport without any extrinsic symmetry breaking in the non-centrosymmetric monolayer and trilayer MoS2 by purely electronic means, whereas no valley signal is detected for centrosymmetric bilayer MoS2.